Pengaruh Efektivitas Sistem Informasi Pasar Kerja Online terhadap Kualitas Pelayanan Publik di Dinas Tenaga Kerja dan Transmigrasi Provinsi Sumatera Barat - Dona Restetya; Dasman Lanin (PUBLICNESS: Journal of Public Administration studies, 2022)
This study aims to determine how much influence the effectiveness of the online job market information system and the linkage of the online market information system to public services at the Transmigration Service of West Sumatra Province. This study uses quantitative associative methods, quantitative data coIlected using a Likert scale questionnaire that has been tested for vaIidity and reliability. The population of this study were individuals who were registered as job seekers in the Online Job Market Information System as many as 1500 people, the sample obtained in this study was obtained by 94 respondents using the Slovin formula (10% error) then analyzed using simple linear regression. . In this study, it can be seen that there is a positive and significant influence between the independent variables, namely the effectiveness of the online job market information system on the dependent variable, namely the quality of service that has been tested with a significance of 0.000, smaller than <0.05. The percentage contribution of variable X to Y is 53.2%.